Research and prospect of binary high-temperature Pb-free solders. Issue 1 (2nd February 2015) - Du, Yunfei; Li, Chuntian; Huang, Bin; Tang, Ming; Du, Changhua
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to identify a variety of binary system solders by alloying, and relevantly derive multiple system Pb-free solders from the former, attempting to replace the high temperature Sn-Pb solder. Design/methodology/approach – The basis of the paper is the synthesis of previous studies. In terms of some binary high temperature solder alloys, such as Au-20Sn, Bi-2.5Ag, Sn-5Sb, Au-12.5Ge, Zn-6Al and Zn-Sn, taking the alloy phase diagram as the starting point, the melting characteristics, microstructure, mechanical properties, wetting ability and reliability of solder joint are analysed and the prospect is consequently indicated. Findings – Based on the analysis of the six groups of Pb-free solders, the present binary system solder alloys, from the perspective of melting properties, mechanical properties, soldering or reliability of solder joint, rarely meet the comprehensive requirements of replacing the high-temperature Sn-Pb solder. It is assumed to be a solution that multiple-system Pb-free solders derive from a variety of binary system solders by means of alloying. The future development of high temperature Pb-free solder may focus on some factors such as physical properties, mechanical properties, processing, reliability of solder joint, environmental performance and expense. Originality/value – The paper concentrates on the issue of Pb-free solders at high temperature. From a specific perspective of binary system solders, the presently available Pb-free solders are suggested from the starting point of the alloy phase diagram and the prospect of alternatives of Sn-Pb solders at high temperature are indicated.